(untitled) (Revista Innova Educación, 2019)
The purpose of this article was to identify personal empathy in the poem "Soy el otro" by Boris Espezúa. The method of study that was used was the hermeneutics based on the description and reflection of the text or discourse, for it is counted in the account of phenomenology, the contribution of structuralism and the study of signs. The study technique that was applied was the analysis of the poetic discourse oriented in the textual, enunciative, semiotic and pragmatic dimension. Therefore, this work concluded that there is a manifestation of personal empathy, since the lyrical subject is externalized by the ability to be sociable, to establish good interpersonal relationships and to know others.